2017
DOI: 10.1097/md.0000000000007916
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting dysphagia after anterior cervical surgery

Abstract: A multicenter retrospective study.The purpose of this study was to explore risk factors of dysphagia after anterior cervical surgery and factors affecting rehabilitation of dysphagia 2 years after surgery.Patients who underwent anterior cervical surgery at 3 centers from January 2010 to January 2013 were included. The possible factors included 3 aspects: demographic variables—age, sex, body mass index (BMI): hypertension, diabetes, heart disease, smoking, alcohol use, diagnose (cervical spondylotic myelopathy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 12 publications
2
26
1
Order By: Relevance
“…In our study, dysphagia was the most common complication of ACDF with a 3.3% incidence rate and obesity was significantly associated with the development of swallowing difficulties (4.1% vs. 3.22%; OR, 1.121; 95% CI, 1.032–1.218; p = 0.0071). In a retrospective multicenter study of 2,827 ACDFs, Wang et al [ 30 ] also found that patients who developed immediate postoperative dysphagia had a higher BMI than those who did not (27.3 vs. 24.6 kg/m 2 , p ≤ 0.001). Liu et al [ 27 ] reported a similar result during the first to second postoperative days.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, dysphagia was the most common complication of ACDF with a 3.3% incidence rate and obesity was significantly associated with the development of swallowing difficulties (4.1% vs. 3.22%; OR, 1.121; 95% CI, 1.032–1.218; p = 0.0071). In a retrospective multicenter study of 2,827 ACDFs, Wang et al [ 30 ] also found that patients who developed immediate postoperative dysphagia had a higher BMI than those who did not (27.3 vs. 24.6 kg/m 2 , p ≤ 0.001). Liu et al [ 27 ] reported a similar result during the first to second postoperative days.…”
Section: Discussionmentioning
confidence: 99%
“…A predominance in that plate-cage group without clinical significance was noted in that study [11]. Wang et al reported a higher number of dysphagia reaching 20% in the post-operative period [12]. Moreover, Riley et al reported dysphagia rates up to 30% of their population, and it increased with the increase of number of levels instrumented [13].…”
Section: Discussionmentioning
confidence: 75%
“…The comorbidity burden in ACDF procedures has increased over time [ 1 ]. The following comorbidities were identified as independent risk factors for the development of dysphagia by our study and many others: smoking [ 26 , 27 ], fluid and electrolyte disorders [ 9 , 16 ], paralysis [ 9 , 16 ], coagulopathy, neurodegenerative diseases [ 9 ], alcohol abuse [ 9 , 16 ], diabetes with chronic complications [ 28 ], depression and psychosis [ 9 , 16 , 28 ]. In contrast to some studies regarding obesity [ 6 , 27 , 29 ], our results showed that body mass index was significantly associated with dysphagia.…”
Section: Discussionmentioning
confidence: 93%
“…In contrast, the data from our report shows dysphagia was less frequent in the global female population, a result comparable to the retrospective analysis by Riley et al [ 24 ] and the NIS database review by Singh et al [ 9 ]. Additionally, previous data suggested age as an independent risk factor for postoperative dysphagia [ 7 , 9 , 15 , 23 , 25 , 26 ]. Our results appear to be congruent with these previous studies, with a 5.9-year age increase seen in the dysphagia group.…”
Section: Discussionmentioning
confidence: 99%